Perceived Value, Store Image and Satisfaction as Antecedents of Store Loyalty Moderated by Procedural Switching Costs - Wiardi, Akram Harmoni; Hadi, Effed Darta; Novrianda, Herry (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
The phenomenon of measuring behavioral loyalty on specific stores or merchants obviously popular, particularly despite the existence of structural and fundamental criticism on specific issue. The objectives of this research is to examine the antecedents of customer loyalty specifically on store loyalty. We operate survey method to gather primary data. The focus of the research is to examine the effect of perceived value, store image, and customer satisfaction on store loyalty. The results indicate that customer who perceive low perception of procedural switching costs and high perception of procedural switching costs experienced different perception in their perceived value on customer satisfaction, perceived value on loyalty, and store image on customer satisfaction. The results shows that the perceived value, store image, and customer satisfaction has a positive and significant relationship of store loyalty in the different perception of procedural switching costs. Furthermore, procedural switching costs play a significant role in moderating the relationship between customer satisfaction and store loyalty. There was an indirect effect in the relationship between perceived value and store loyalty, which was mediated by customer satisfaction. The indirect effect of the relationship between store image and store loyalty was also proven to be mediated by the customer satisfaction.